2015
DOI: 10.1371/journal.pone.0121568
|View full text |Cite
|
Sign up to set email alerts
|

The Growth and Aggressive Behavior of Human Osteosarcoma Is Regulated by a CaMKII-Controlled Autocrine VEGF Signaling Mechanism

Abstract: Osteosarcoma (OS) is a hyperproliferative malignant tumor that requires a high vascular density to maintain its large volume. Vascular Endothelial Growth Factor (VEGF) plays a crucial role in angiogenesis and acts as a paracrine and autocrine agent affecting both endothelial and tumor cells. The alpha-Ca2+/Calmodulin kinase two (α-CaMKII) protein is an important regulator of OS growth. Here, we investigate the role of α-CaMKII-induced VEGF in the growth and tumorigenicity of OS. We show that the pharmacologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Transcription factors control the expression of a given gene by serving as integration centers of different signaling cascades26. Many transcription factors regulate VEGF transcription and expression272829. Daft et al 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors control the expression of a given gene by serving as integration centers of different signaling cascades26. Many transcription factors regulate VEGF transcription and expression272829. Daft et al 27.…”
Section: Discussionmentioning
confidence: 99%
“…Many transcription factors regulate VEGF transcription and expression272829. Daft et al 27. found that the inhibition of CaMKII and VEGFR decreased HIF-1α and AP-1 binding to the VEGF promoter, which is likely responsible for the observed decreases in VEGF transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that chronic ischemia has a direct association with coronary angiogenesis, but the underlying molecular mechanisms are unclear [23,24]. It has been shown that CaMKII inhibition blunted tumor response to hypoxia [17] and that CaMKII is likely the upstream signal of the hypoxia inducible factor-1 alpha (HIF-1α) in macrophage and some cancer cell lines [14][15][16]. Indeed, oxidative stress and calcium entry caused by repetitive ischemia can both activate CaMKII [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The primary promoters of VEGF are HIF-1α and activating protein-1 (AP-1). CaMKII was able to up-regulate the expression of HIF-1α in marcrophage [14] and retinal Müller cells [31], and increase AP-1 protein level in osteosarcoma [15]. However, there was study showed that CaMKII inhibitor had no effect on HIF-1α induced VEGF production in rheumatoid synovial fibroblast [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation